Temporal trend and spatial distribution of Chagas disease in the Northern Region of Brazil: an alert for the state of Pará - Neves, Karen Nickole Sousa; Rosário, Julianne Beathriz Abdon do; Abdon, Bruna Lima; Guimarães-Costa, Aurycéia Jaquelyne (Revista JRG de Estudos Acadêmicos, 2025)
This study analyzed the temporal trend and spatial distribution of Chagas disease (CD) cases in the Northern Region of Brazil between 2013 and 2023, using data from the Notifiable Diseases Information System (SINAN/DATASUS). Confirmed cases of acute CD reported in the seven states of the region were included, and variables such as state of residence, sex, age group, and municipality were examined. The results revealed marked regional heterogeneity. Pará accounted for 79% of all notifications, totaling 2,688 cases, with notable concentrations in municipalities such as Abaetetuba, Breves, Belém, Cametá, and Curralinho, which represented true transmission hotspots. A significant increase in notifications was also observed after 2020, following a decline coinciding with the critical period of the COVID-19 pandemic. Age-group analysis showed greater involvement among adults aged 20 to 59 years, a group associated with the processing and consumption of regional foods such as açaí, the main product implicated in oral transmission in the Amazon. The distribution between sexes was balanced, suggesting a community-level exposure pattern. In the other states, low-notification profiles were observed, with small clusters in Amazonas, Amapá, Acre, and Tocantins, while Rondônia and Roraima reported minimal numbers, possibly influenced by underreporting and structural limitations in surveillance. The findings reinforce that CD remains a major public health challenge in the Northern Region, particularly in Pará, where productive, socioenvironmental, and structural factors combine to sustain the circulation of Trypanosoma cruzi. The results highlight the need for continuous surveillance, strengthening of Primary Health Care, improvement of sanitary practices in açaí processing, and expansion of diagnostic capacity to reduce transmission and enhance early disease detection.